The ATP sensitive potassium channel (KATP) is a novel target for migraine drug development - Clement, Amalie; Christensen, Sarah Louise; Jansen-Olesen, Inger; Olesen, Jes; Guo, Song (Frontiers in Molecular Neuroscience, 2023)
Migraine is one of the leading causes of disability worldwide, affecting work and social life. It has been estimated that sales of migraine medicines will reach 12,9 billion USD in 2027. To reduce social impact, migraine treatments must improve, and the ATP-sensitive potassium (KATP) channel is a promising target because of the growing evidence of its implications in the pathogenesis of migraine. Strong human data show that opening of the KATP channel using levcromakalim is the most potent headache and migraine trigger ever tested as it induces headache in almost all healthy subjects and migraine attacks in 100% of migraine sufferers. This review will address the basics of the KATP channel together with clinical and preclinical data on migraine implications. We argue that KATP channel blocking, especially the Kir6.1/SUR2B subtype, may be a target for migraine drug development, however translational issues remain. There are no human data on the closure of the KATP channel, although blocking the channel is effective in animal models of migraine. We believe there is a good likelihood that an antagonist of the Kir6.1/SUR2B subtype of the KATP channel will be effective in the treatment of migraine. The side effects of such a blocker may be an issue for clinical use, but the risk is likely only moderate. Future clinical trials of a selective Kir6.1/SUR2B blocker will answer these questions.